2022
DOI: 10.1186/s13089-022-00282-6
|View full text |Cite
|
Sign up to set email alerts
|

Increasing illness severity is associated with global myocardial dysfunction in the first 24 hours of sepsis admission

Abstract: Background Septic cardiomyopathy was recognized more than 30 years ago, but the early phase remains uncharacterized as no existing studies captured patients at the time of Emergency Department (ED) presentation, prior to resuscitation. Therapeutic interventions alter cardiac function, thereby distorting the relationship with disease severity and outcomes. The goal of this study was to assess the impact of illness severity on cardiac function during the first 24 h of sepsis admission. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Sepsis remains one of the leading causes of intensive care unit (ICU) mortality in the United States (U.S.) [ 1 ]. Cardiac dysfunction or sepsis-induced cardiomyopathy commonly occurs in this patient population, albeit with little consensus on appropriate definition for sepsis cardiomyopathy [ 2 ] and can be seen in up to 40–60% and has been shown to be associated with worse outcomes [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis remains one of the leading causes of intensive care unit (ICU) mortality in the United States (U.S.) [ 1 ]. Cardiac dysfunction or sepsis-induced cardiomyopathy commonly occurs in this patient population, albeit with little consensus on appropriate definition for sepsis cardiomyopathy [ 2 ] and can be seen in up to 40–60% and has been shown to be associated with worse outcomes [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It represents a more sensitive tool to spot subtle or early myocardial dysfunction. 35 This may prealert clinicians and impact their plans. However, STE requires high image quality, which is sometimes difficult to obtain in acute settings.…”
Section: Aortic Stenosis (As)mentioning
confidence: 99%
“…Data on LVEF were available for thirteen of the fourteen studies included in the primary analysis [21][22][23][24][25][26][28][29][30][31][32][33][34] and showed a signi cant association between mortality and lower LVEF (MD:2.44%; [0.44,4.45]; p=0.02; I 2 =42%; Figure 3). A post-hoc analysis considering only the six studies clearly stating they used the Simpson's method for LVEF quanti cation resulted in no association between LVEF and survival (MD:2.51% [-0.60,5.62]; p=0.11; I 2 =45%).…”
Section: Secondary Outcome -Lvef and Mortality At Longest Follow-upmentioning
confidence: 99%
“…After excluding 16 studies (in nine cases for overlap with subsequent publications), 13 new studies were included, but ve of them were included in the sensitivity analysis only. Hence, we included in the primary analysis eight studies identi ed by the update search, and the six studies already included in the previous metanalysis, resulting in a pool of 14 studies [21][22][23][24][25][26][27][28][29][30][31][32][33][34]. One of the included studies reported GLS at three time-points, and we chose the GLS at 24 hours, leaving the data collected at 0 and 3 hours for a sensitivity analysis [30].…”
Section: Study Selectionmentioning
confidence: 99%